2000
DOI: 10.1016/s0014-5793(00)01819-6
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases 19 and 20 cleave aggrecan and cartilage oligomeric matrix protein (COMP)

Abstract: Matrix metalloproteinase (MMP)-19 and MMP-20 (enamelysin) are two recently discovered members of the MMP family. These enzymes are involved in the degradation of the various components of the extracellular matrix (ECM) during development, haemostasis and pathological conditions. Whereas MMP-19 mRNA is found widely expressed in body tissues, including the synovium of normal and rheumatoid arthritic patients, MMP-20 expression is restricted to the enamel organ. In this study we investigated the ability of MMP-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
85
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 43 publications
(72 reference statements)
0
85
0
2
Order By: Relevance
“…Purified COMP has been reported to be digested by several matrix metalloproteinases (MMPs), including interstitial collagenase (MMP-1), collagenase-3 (MMP-13), stromelysin-1 (MMP-3), gelatinase-B (MMP-9), MMP-19, and enamelysin (MMP-20) (60). Recently, it was found that ADAMTS-4 can also cleave purified COMP in vitro (61); in this study, we present evidence showing that both the recombinant catalytic domain and intact ADAMTS-7 also digest COMP in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Purified COMP has been reported to be digested by several matrix metalloproteinases (MMPs), including interstitial collagenase (MMP-1), collagenase-3 (MMP-13), stromelysin-1 (MMP-3), gelatinase-B (MMP-9), MMP-19, and enamelysin (MMP-20) (60). Recently, it was found that ADAMTS-4 can also cleave purified COMP in vitro (61); in this study, we present evidence showing that both the recombinant catalytic domain and intact ADAMTS-7 also digest COMP in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…6 The catalytic domain of MMP19 degrades various ECM components including collagen type IV, nidogen-1, fibronectin, tenascin-C isoform, aggrecan, and laminin-5-gamma-2-chain. [7][8][9] The catalytic domain contains the typical zinc-binding motif; the zinc and calcium ions additional to this domain are necessary for structure stability and enzymatic activities of MMPs. 10 The glutamate residue at the zinc binding motif activates the zinc-bound water molecule to provide the nucleophile during cleaving activities on peptide bonds.…”
mentioning
confidence: 99%
“…[26][27][28] MMP19 is able to cleave several components of the extracellular matrix such as collagen IV, nidogen, tenascin C, laminin 5g2, fibronectin, cartilage oligomeric protein, aggrecan, and secreted insulin-like growth factor binding protein 3, thus modulating IGF signaling pathway. 25,[29][30][31][32] In this study, we evaluated the expression of MMP19 in cutaneous melanoma at different stages of progression using immunohistochemistry. We found that the expression of MMP19 increases during the melanoma progression and that MMP19 activity facilitates the migration of tumour cells.…”
mentioning
confidence: 99%